Anaesthesia during Carotid Endarterectomy and Urinary Neopterin. (17th October 2012) - Rerkasem, K.; Shearman, C. P.
Abstract : Recent systematic reviews of randomized controlled trials show that the rate of postoperative complications after carotid endarterectomy (CEA) was not significantly different between operations performed under general anesthesia (GA) or local anesthesia (LA). However, these studies were not large enough to draw meaningful conclusions about any difference in mortality. This study therefore aimed to compare a surrogate endpoint of postoperative mortality between GA and LA by using urinary neopterin. 68 consecutive patients admitted electively for CEA were studied. Urinary neopterin levels were assayed preoperatively, immediately postoperatively (PO), 4, 6, 12, and 24 hrs PO. This study compared the level of urinary neopterin between GA and LA. Of the 68 CEAs, 48 operations were performed under GA. Urinary neopterin concentration in LA group increased PO and reached a peak at 6 hrs PO. At this point, the urinary neopterin levels in the GA group (85.3 μ mol/mol creatinine) were significantly lower than those under the LA group (123.4 μ mol/mol creatinine) (P = 0.02 ). We found that the level of urinary neopterin level after operation in LA was significantly higher than those under GA. More studies are needed.